DAMPAK PERMINTAAN BBM TERHADAP DISTRIBUSI PENDAPATAN RUMAH TANGGA INDONESIA: Pendekatan Social Accounting Matrices (SAM) 2008 - , Jamara Ramhot Jaya Damanik; , Dr. Tri Widodo, M.Ec. Dev ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The purpose of this research is to evaluate the demand for fuel based on household income and also to find characteristics of household distribution in Indonesia in the SAM in the year 2008. The outcome of the research is expected to be useful in the planning development of energy sector especially fuel and also useful for SAM analysis. The information that isused is secondary information. It is taken from Indonesian Social Accounting Matrices System and analyzed with Social Accounting Matrices. The research has shown a results that effect of the multiplier with the simulation of the increase in demand approximately one billion demand based on households distribution has a high value of multiplier to household not agricultural in cities, but free lancers, non agriculture business people, managers, military, professionals, technician, teachers, clerical workers and professional seller. Increase in output in production sector when there is an increase in demand of fuel in mining sector such as coals, metal ore and crude oil have the highest multiplier value. Increase in the demand of petrol approximately one billion based on the production factor, there is an intensive works/employees to non employees. The increase in output in production sector for all kinds of goods and services commodity. This indicates the high demand and of fuel in Indonesia.